The Impact Of Telework On Knowledge Creation And Management - Watad, Mahmoud M.; Jenkins, Gregory T. (Journal of Knowledge Management Practice, 2010)
This paper examines the dynamics of knowledge management in a virtual environment. It focuses on both, the ways telework alters knowledge creation and, the performance implications of this alteration. One of the main unintended consequences of telework is that it changes the dynamics of knowledge creation and knowledge sharing. Telework may hinder the creation of tacit knowledge as it eliminates the faceto-face communication and interactions that are found in a typical office setting. Members of an organization working in a telework environment spend most of their time creating and sharing explicit rather than tacit knowledge. This shift in the creation of knowledge has long-term implications on organizational performance and effectiveness. According to this study, there is evidence, albeit not conclusive, that virtual work arrangements contribute to the reduction of an organization’s effectiveness, mainly through a reduction in the creation of tacit knowledge. There is a growing number of managers who realize that telework should be approached not as a narrow-scope innovation but as an initiative that impacts all aspects of an organization, including knowledge management.
Keywords: knowledge management; Telework; Knowledge creation; Tacit knowledge; Virtual work arrangements